Obtenção de extratos padronizados a partir das cascas de Stryphnodendron adstringens (Mart.) Coville (Fabaceae) e avaliações biológicas in vitro - Sousa, Jordana Nunes de (2014)
The present work aimed to obtain extracts from the barks of Stryphnodendron adstringens (Mart) Coville (Fabaceae) and evaluating of biological activities in vitro, from them. Chapter 1 using pharmacopoeial and not pharmacopoeial methods; barks, powder and liquid extract of S. adstringens were characterized and then a HPLC method was developed and validated to idenfication of epigallocatechin gallate (EGCG) at extracts. In Chapter 2, described the cytotoxic activity of the dry extract of S. adstringens, obtained by atomization, and the EGCG standard against L929 fibroblast cells by the method of neutral red. EGCG at 200 µg/mL reduced, p ≤ 0.05, the cell viability of L929 fibroblasts to 47.70%, such as the dried extract of S. adstringens at 225 mg/mL. Chapter 3 presented the obtainment of dry extracts of S. adstringens by atomization. The influence of the proportion of adjuvant drying, the drying air temperature and flow rate of the drying air on total phenols, EGCG, tannins, total antioxidant activity and efficiency of the drying process were evaluated, the significant results (p≤0.05) were obtained by ANOVA and represented by response surface methodology. The increase in the adjuvant drying was not significantly favorable to efficiency of the drying process. Increasing the temperature of the drying air had a quadratic behavior negative to total phenols and positive to total tannins. The increasing of flow air drying showed linear and quadratic behavior. negative to total antioxidant activity. The efficiency of the drying process was not influenced by any variable. The dried extracts were analyzed for their content of volatile, water activity and the morphologies of the particles were observed by scanning electron microscopy. In Chapter 4 we describe the optimization of extraction of total phenols, tannins and epigallocatechin gallate powders of barks of S. adstringens ultrasonic using Box- planning Benhken 33. The use and validation of the desirability global statistical showed that the proportion of ratio drug solvent 4mg/mL, time extraction 30 min and the 65 % (v/v) hydroalcoholic solution are ideal to simultaneous extraction of these metabolites. The results indicate that the extracts were obtained and standardized quality, and have potential to be investigated their biological and/or insertion activities in herbal formulations